Prevalence of Occupational Asthma and Respiratory Symptoms in Foundry Workers - Kayhan, Servet; Tutar, Umit; Cinarka, Halit; Gumus, Aziz; Koksal, Nurhan (Pulmonary Medicine, 2013)
This cross-sectional study was conducted in a foundry factory to assess the prevalence of respiratory symptoms and occupational asthma in foundry workers. Physical examination, spirometric evaluation, chest radiograph, and a questionnaire related to respiratory symptoms were performed. Monitoring of peak expiratory flow rates, spirometric reversibility test, and high-resolution computed tomographies were performed for the participants having respiratory symptoms and/or impaired respiratory function test. A total of 347 participants including 286 workers from production department and 61 subjects who worked in nonproduction departments were enrolled in this study. It is found that phlegm (n: 71, 20.46%) and cough (n: 52, 14.98%) were the most frequent symptoms. The other symptoms were breathlessness (n: 28, 8.06%), chest tightness (n: 14, 4.03%), and wheezing (n: 7, 2.01%) . The prevalence of occupational asthma was found to be more frequent among the subjects who worked in the production department (n: 48, 16.78% ) than the other persons who worked in the nonproduction department (n: 3, 4.91%) by chi-square test (P: 0.001). To prevent hazardous respiratory effects of the foundry production, an early diagnosis of occupational asthma is very important. Cessation of cigarette smoking and using of protective masks during the working time should be encouraged.